Enhanced pathogenicity and synergistic effects of co-infection with bovine viral diarrhea virus 1 and HoBi-like virus in cattle and guinea pigs - Cui, Hongliang; Ren, Baoru; Wang, Linglong; Chen, Jian; Li, Jie; Hu, Wei; Yang, Yang (Frontiers in Veterinary Science, 2024)
IntroductionThe Bovine Viral Diarrhea Virus 1 (BVDV1) and HoBi-like virus (BVDV3), both within the same genus, share genomic homology and exhibit low antigenic cross-reactivity despite presenting similar clinical manifestations. In 2021, a bovine respiratory disease complex (BRDC) outbreak on two cattle farms in the Inner Mongolia Autonomous Region of China resulted in ten fatalities.MethodsMetagenomic and metatranscriptomic analyses were used to identify viral agents, including a co-infection case. A genetic evolution analysis assessed the relationships with related strains. Experimental infections in guinea pigs and calves evaluated the pathogenicity of the virusesResultsPhylogenetic analysis of the BVDV3 isolate IM2201 revealed close relatedness to Brazilian strains, with 97.06% nucleotide homology to the highly virulent strain SV478/07. Experimental co-infection in guinea pigs resulted in more severe clinical signs, including fever, cough, diarrhea, and significant pathological changes, and led to a higher mortality rate (40%) compared to no mortality from single-virus infections with BVDV1 or BVDV3. Similarly, co-infected cattle exhibited more severe clinical signs, including bloody diarrhea and rectal temperatures exceeding 40°C, along with persistent viremia and nasal viral shedding from 7 to 21 days post-infection. Blood analysis revealed significant reductions in white blood cell counts, particularly in co-infected cattle.DiscussionThis study highlights the enhanced pathogenicity and synergistic effects of BVDV1 and BVDV3 co-infection, exacerbating disease severity.